Variability of preoperative rehabilitation in preparation for primary arthroplasty in patients with osteoarthritis of the knee joint - G. P. Kotel'nikov; A. V. Kolsanov; O. I. Moseev; D. S. Kudashev; S. D. Zuev-Ratnikov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. In the last decade, preoperative rehabilitation has attracted considerable attention from both domestic and foreign specialists, however, its effectiveness and impact on the early recovery of patients with osteoarthritis of the knee joint after primary arthroplasty causes many contradictions and remains controversial.Objective. To analyze the scientific literature and evaluate the results, potential advantages and disadvantages of using available and modern methods of preoperative rehabilitation in preparation for primary arthroplasty in patients with osteoarthritis of the knee joint.Materials and methods. In the course of this study, data was searched using Scopus, Web of Sciеnce, Pubmed, and RSCI databases for the period from 2009 to 2024.Results. As a result of the analysis, the key methods of preoperative rehabilitation used during the preparation for total knee arthroplasty were identified, and the effect of these methods on the restoration of functional parameters in patients, changes in pain and the duration of hospital stay after surgery was studied in comparison with the standard program of preparation for total knee arthroplasty.Conclusion. During the study, it was revealed that preoperative rehabilitation before total knee replacement can significantly reduce the duration of hospital stay, however, convincing evidence of improvement in postoperative functional parameters has not been established. To determine the real effectiveness of preoperative rehabilitation, clinical studies are needed to study the effect of comprehensive preoperative rehabilitation programs on the pathogenetic aspects of osteoarthritis, clinical symptoms and functional parameters in the postoperative period.